2000
DOI: 10.1017/s0967199400000952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gap junction uncoupling in full-grown Bufo arenarum ovarian follicles: participation of cAMP in meiotic arrest

Abstract: The aim of the present study was to determine the presence of the connexins Cx43, Cx32 and Cx26 in Bufo arenarum ovarian follicles during the breeding season as well as to analyse the possible alterations in the meiotic process when connexins are blocked by specific antibodies. Western blot analysis revealed that the Cx43 and Cx32 proteins were present but not Cx26. We demonstrated that the anti-Cx43 and anti-Cx32 antibodies produced the uncoupling of the gap junctions. When these junctions are blocked the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Their closure appeared to inhibit the supply of MIS from the granulosa cells to the oocytes, and consequently induced the resumption of meiosis. A similar phenomenon was reported in the South American toad (Bufo arenarum), in which the oocytematuration process was triggered when the GJs were blocked (Villecco et al, 2000). Moreover, the disruption of GJs between oocytes and follicle cells is necessary for the LH-dependent resumption of oocyte meiosis in the ovarian follicles of mammals (for a review, see Dekel, 2005).…”
Section: Introductionsupporting
confidence: 60%
“…Their closure appeared to inhibit the supply of MIS from the granulosa cells to the oocytes, and consequently induced the resumption of meiosis. A similar phenomenon was reported in the South American toad (Bufo arenarum), in which the oocytematuration process was triggered when the GJs were blocked (Villecco et al, 2000). Moreover, the disruption of GJs between oocytes and follicle cells is necessary for the LH-dependent resumption of oocyte meiosis in the ovarian follicles of mammals (for a review, see Dekel, 2005).…”
Section: Introductionsupporting
confidence: 60%
“…Several investigators have proposed cAMP to be one of the molecules involved in meiotic arrest (Eppig & Downs, 1984; Tsafriri et al ., 1996; Chen et al ., 2009). In the anuran Bufo arenarum oocytes we demonstrated that cAMP exerts an inhibitory effect on the maturation induced by the uncoupling of gap junctions when oocytes are pretreated with octanol (Villecco et al ., 2000). However, there is no detailed information concerning cAMP participation during X. laevis vitellogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This presumably represents the contribution from the oocyte to the vitelline envelope, as seen in the cytological manifestation of the accumulation of dense vesicles in its cytoplasm, as suggested to occur in Bufo arenarum by Cabada et al (1996). Participation of the follicular epithelium in the formation of vitelline envelope has been suggested by Wallace and Jared (1976) and Dumont and Brummett (1978) in X. laevis, by Cabada et al (1996) in B. arenarum, by Villecco et al (2000) in C. cranwelli and by Sretarugsa et al (2001) in R. tigrina.…”
Section: Discussionmentioning
confidence: 85%
“…These variations are attributable to the adaptational requirements of the species to the diverse environments in which they lay their eggs and thus secure their development (Guraya 1976(Guraya , 1979Del Pino et al 1986;Del Pino 1989;Villecco et al 1996Villecco et al , 1999Villecco et al , 2000Villecco et al , 2002Uribe 2001Uribe , 2003Sanchez and Villecco 2003;Exbrayat 2006). A definite number of primordial follicles are established in the embryo (Skinner 2005).…”
Section: Introductionmentioning
confidence: 99%